The biological efficiency and bioavailability of human growth hormone delivered using injectable, ionic, thermosensitive poly(organophosphazene)-polyethylenimine conjugate hydrogels - Seo, Bo-Bae; Park, Mi-Ran; Chun, Chan; Lee, Jae-Yeol; Song, Soo-Chang (ELSEVIER SCI LTD, 2011)
We have endeavored to develop injectable, thermosensitive, biodegradable hydrogels that prolong human growth hormone (hGH) release, improving bioavailability through introducing balanced ionic interactions. Cationic poly(organophosphazene)-polyethylenimine (PEI, 1.8 kDa) conjugate hydrogels were synthesized as those hydrogels for sustained delivery of anionic hGH with proper ionic strength of association/dissociation. We have additionally prepared different chain lengths of alpha-amino-omega-methoxy-poly(ethylene glycol) (AMPEG550 and AMPEG750) for the synthesis of conjugates as a means to control hydrogel degradation rates. All Aqueous solutions of PEI-conjugates became hydrogels hydrolyzable in proportion to AMPEG molecular weight at body temperature; these PEI-conjugates complexed with hGH and extended hGH release in vitro. In pharmacokinetic studies of hGH behavior in SD rats, hydrogels of PEI-conjugate/hGH complexes could suppress the initial burst-phase, and extend the duration, of release, as well as increasing of area under the curve (AUC) compared to controls including hGH solution or nonionic hydrogel. In a hypophysectomized rat model, the biological efficacy of hGH delivered from PEI-conjugate/hGH complex hydrogels was equivalent to that from daily administration over four days based on body weight gain and width of the tibial growth plate. These results suggest that ionic, thermosensitive, poly(organophosphazene)-PEI-conjugate hydrogel demonstrates potential as an injectable depot for sustained delivery of bioavailable hGH. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: PROTEIN DELIVERY; GENE DELIVERY; IN-VIVO; RELEASE; FORMULATION; MICROPARTICLES; MICROSPHERES; SYSTEMS